Weaning and postweaning management of dairy replacement heifers. Issue 10 (29th November 2018) - Sherwin, Virginia; Remnant, John
Abstract : Heifer rearing represents approximately 20 per cent of a dairy farm's total cost, but it is often an area with many potential inefficiencies. There is a lot of scope for veterinarians to be involved in the management of postweaning heifers to help drive performance improvement on dairy farms. This article discusses preparing for weaning, the weaning process and postweaning management of the replacement dairy heifer.